2020
DOI: 10.21037/jtd-20-671
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and accuracy of rapid on-site evaluation of touch imprint cytology during transbronchial biopsy

Abstract: Background: Rapid on-site evaluation (ROSE) of cytologic material is widely performed because it provides clinicians with instant diagnostic information. However, the utility of ROSE of touch imprint cytology (ROSE-TIC) during transbronchial biopsy (TBB) remains unclear. The aim of this study was to evaluate the feasibility and accuracy of ROSE-TIC for TBB. Methods: A retrospective study was performed on patients who underwent diagnostic bronchoscopy combined with ROSE-TIC. The results of ROSE-TIC, diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…However, even when the sampling is not cytological but histological (e.g., endobronchial forceps biopsy, core needle biopsy) the agile cytopathologist can employ quick cytological techniques for rapid on-site evaluation and specimen triage [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Small biopsies can be used to prepare the whole array of cytological specimens in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…However, even when the sampling is not cytological but histological (e.g., endobronchial forceps biopsy, core needle biopsy) the agile cytopathologist can employ quick cytological techniques for rapid on-site evaluation and specimen triage [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Small biopsies can be used to prepare the whole array of cytological specimens in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of ROSE has been evaluated in various studies on material taken by EBUS‐TBNA with a variety of results. However, there are few studies that investigate the utility of ROSE during conventional bronchoscopy with FOB, 16,17 this is probably because this procedure is currently considered to be useless for visible lesions on FOB with respect to the commitment of human resources and time required. This therefore represents an important limitation for many laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between ROSE on TIC and/or on brushing and endobronchial biopsy for immunohistochemical and molecular predictive testing has not yet specifically been addressed. The study by Shikano et al 17 has shown high accuracy between ROSE by TIC and histology, as well as its value for obtaining a high‐success rate of molecular analysis for target therapy. Our data is similar for predictive testing, but discordant for diagnostic accuracy, which reported a higher level of sensitivity, specificity, and accuracy than our results have.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Moreover, the accuracy of ROSE with both histological diagnosis using EBUS-GS and final pathological findings was approximately 80% to 90% for diagnosing such lesions. [19][20][21] Therefore, if ROSE during EBUS-GS for small peripheral lung cancer did not include malignant cells when the probe was located either within or adjacent to the lesion, the bronchoscopic diagnosis had a high possibility of failure. Identification of factors that affected the results of ROSE during EBUS-GS in such a probe position might contribute toward performing additional devices during EBUS-GS, which might lead to overcome the lower diagnostic yield.…”
Section: Introductionmentioning
confidence: 99%